2021
DOI: 10.2147/idr.s318787
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Plasmid-Mediated Mobile Colistin Resistance Gene (mcr-1) in Enterobacterales Isolates from a University Hospital

Abstract: Purpose Colistin represents one of the last treatment options for infections caused by multi-drug resistant (MDR) Enterobacterales . The emergence of a plasmid-mediated mobile colistin resistance-1 ( mcr-1 ) gene has raised serious concerns about its potential dissemination among bacteria. Methods In this study, we evaluated the chromogenic medium, CHROMID ® Colistin Resistance (COLR) agar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 40 publications
1
17
2
Order By: Relevance
“…However, higher than detected by El-Sokkary et al 24 study where 2.79% CRE was colistin resistant. However, our results are much lesser than that regarding Anan et al 25 study, who detect 75% of K. pneumoniae isolates were colistin resistant by BMD.…”
Section: Table (5): Antibiotic Susceptibility Of Cpkp In Relation Tocontrasting
confidence: 92%
“…However, higher than detected by El-Sokkary et al 24 study where 2.79% CRE was colistin resistant. However, our results are much lesser than that regarding Anan et al 25 study, who detect 75% of K. pneumoniae isolates were colistin resistant by BMD.…”
Section: Table (5): Antibiotic Susceptibility Of Cpkp In Relation Tocontrasting
confidence: 92%
“…These results are similar to studies in Egypt [23,25]. On the other hand, other studies showed that some negative isolates in PCR exhibited phenotypic colistin resistance in MIC [24,26].…”
Section: A Single E Coli Isolates Harbored the Mcr-1 Genesupporting
confidence: 90%
“…Broth micro dilution (BMD) was recommended as the standard procedure. This standard technique is quite laborious, time-consuming, difficult to interpret, susceptible to mistakes, not suitable for most laboratories 8, 9 . Currently, agar dilution and colistin broth disk elution (CBDE) are acceptable methods 10 .…”
Section: Introductionmentioning
confidence: 99%